LuftiBus in the school (LUIS): a population-based study on respiratory health in schoolchildren (Swiss Medical Weekly, 2021)
Respiratory disease is common in children and strongly associated with lifestyle and environmental exposures. Thus, it is important to study the epidemiology locally. The LuftiBus in the School (LUIS) study was set up to assess the respiratory health of schoolchildren in the canton of Zurich, Switzerland. LUIS is a cross-sectional population-based study that was carried out 2013 to 2016. Children aged 6–17 years living in the canton of Zurich were eligible to participate. All schools in the canton were approached and the school head decided whether the school would participate and with which classes. Consenting parents answered a standardised questionnaire at home and assenting children completed a shorter questionnaire by interview at school. Trained technicians measured children’s lung function, including spirometry, double tracer gas single-breath washout (DTG-SBW) and fractional exhaled nitric oxide (FeNO). Address histories of participants were geocoded to be linked with area-based socioeconomic measures and environmental exposures such as spatiotemporal air pollution estimates for specific time periods and locations. A subgroup was seen again 12 months later using the same procedures to collect longitudinal data. The study included 3870 children at baseline and 655 at the 1-year follow-up. Median age was 12.7 years; 281 (8%) had wheezed in the past year. At baseline we collected 3457 (89%) parental and 3546 (92%) child questionnaires, and 3393 (88%) FeNO, 3446 (89%) spirometry, and 1795 (46%) DTG-SBW measurements. LUIS is a rich resource of health-related data, with information on lung function, environmental exposures and respiratory health on Swiss schoolchildren.